N-Acetylcysteine and Acetylsalicylic Acid Inhibit Alcohol Consumption by Different Mechanisms: Combined Protection - Quintanilla, María Elena; Ezquer, Fernando; Morales, Paola; Ezquer, Marcelo; Olivares, Belen; Santapau, Daniela; Herrera-Marschitz, Mario; Israel, Yedy (Frontiers in Behavioral Neuroscience, 2020)
Chronic ethanol intake results in brain oxidative stress and neuroinflammation, which have been postulated to perpetuate alcohol intake and to induce alcohol relapse. The present study assessed the mechanisms involved in the inhibition of (i) oxidative stress; (ii) neuroinflammation and (iii) ethanol intake, that follow the administration of the antioxidant N-acetylcysteine and the anti-inflammatory aspirin (acetylsalicylic acid) to animals that had consumed ethanol chronically. At the doses used clinically, N-acetylcysteine (40 mg/kg/day p.o.) and aspirin (15 mg/kg/day p.o) significantly inhibited chronic alcohol intake and relapse intake in alcohol preferring rats. Co-administration of both drugs synergically reduced ethanol intake by 65-70%. N-acetylcysteine administration suppressed (a) the hippocampal oxidative stress assessed as the ratio of oxidized glutathione (GSSG)/reduced glutathione (GSH); (b) the neuroinflammation assessed by astrocyte and microglial activation by immunofluorescence and (c) chronic and relapse ethanol intake. These effects were blocked by sulfasalazine, an inhibitor of the xCT transporter, which incorporates intracellular cystine (precursor of GSH) and extrudes glutamate, an agonist of the inhibitory mGLU2/3 receptor, which lowers the glutamatergic tone. The inhibitor of mGLU2/3 receptor (LY 341495) also blocked the N-acetylcysteine-induced inhibition of both relapse ethanol intake and neuroinflammation without affecting the GSSH/GSH ratio. Unlike N-acetylcysteine, aspirin inhibited chronic alcohol intake and relapse via lipoxin A4, a strong anti-inflammatory metabolite of arachidonic acid generated following the aspirin acetylation of cyclooxygenases. Accordingly, the lipoxinA4 receptor inhibitor WRW(4) blocked the aspirin-induced reduction of ethanol intake. Overall, the study shows that different mechanisms of N-acetylcysteine and Aspirin synergize each other, allowing their administration in low doses for the treatment of alcohol use disorders.